Smoothing Module for Optimization Cranium Segmentation Using 3D Slicer - Gilang Argya Dyaksa; Nur Arfian; Herianto Herianto; Lina Choridah; Yosef Agung Cahyanta (International Journal of Applied Sciences and Smart Technologies, 2023)
Anatomy is the most essential course in health and medical education to study parts of human body and also the function of it.  Cadaver is a media used by medical student to study anatomical subject. Because of limited access to cadaver and also due to high prices, this situation makes it necessary to develope an alternative anatomical education media, one of them is the use 3D printing to produce anatomical models. Before 3D Print the cranium, it is necessary to do the segmentation process and often the segmentation result is not good enough and appear a lot of noises. The purpose of this research is  to optimize a 3D cranium based on DICOM (digital imaging and communications in medicine) data processing using the smoothing modules on 3D Slicer. The method of this research is to process the Cranium DICOM data using 3D Slicer software by varying the 5 types of smoothing modules. The results with default parameter fill holes and median have better results compared to others. Kernel size variations are performed for smoothing module fill holes and medians. The result is fill holes get optimal segmentation results using a kernel size of 3 mm and the median is 5 mm